The Urgency of Educational Facilities and Infrastructure Management in Welcoming New Normal Era Learning - Amin, Arifah; Annisaul Khaerani, Tasya; Aprilia, Rezky; Fitriani, Fitriani (DIDAKTIKA, 2023)
The transition into the new normal era following the COVID 19 pandemic presents unique challenges for the education sector, particularly in ensuring safe, effective, and adaptive learning environments. This study explores the urgency of managing educational facilities and infrastructure to support face-to-face learning during the new normal period at UPT SMAN 9 Bone, Indonesia. Employing a qualitative field research design, data were collected through observation, interviews, and documentation involving key school stakeholders. Findings reveal that effective management comprising planning, procurement, inventory, utilization, maintenance, and accountability is crucial for enabling a conducive and health-compliant learning environment. The study also highlights adaptive learning practices such as blended learning, limited face-to-face instruction, and home visits as part of the school's strategy. These findings underscore the strategic role of infrastructure management in maintaining educational continuity and resilience amid post-pandemic transitions.